2012
DOI: 10.1111/j.1600-0609.2011.01747.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical bleeding events and laboratory coagulation profiles in acute promyelocytic leukemia

Abstract: Patients with APL are susceptible to DIC and subsequent bleeding events. Prompt ATRA administration is crucial in preventing hemorrhagic events. High WBC counts, prolonged PT, and APTT are associated with clinical bleeding in our series. PT is the most accurate parameter in predicting bleeding. Based on these findings, supportive care should be directed toward correction of coagulopathy to prevent bleeding complications and fresh frozen plasma appears to be indicated for coagulopathy associated with APL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 21 publications
2
50
0
Order By: Relevance
“…Coagulation disorders are frequently observed in APL and can also occur in other AL subtypes (28)(29)(30). The pathogenic mechanism underlying the blood coagulation disorder in these patients is complex.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation disorders are frequently observed in APL and can also occur in other AL subtypes (28)(29)(30). The pathogenic mechanism underlying the blood coagulation disorder in these patients is complex.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14,[19][20][21] The risk factors identified as independent predictors of severe bleeding in multivariate analysis vary between published studies, and only 3 of those cohorts have .200 participants. With this in mind, uncertainty persists as to what are the best independent predictors of bleeding mortality during induction chemotherapy for APL.…”
Section: Introductionmentioning
confidence: 99%
“…The most important clinical feature of APL is life-threatening hemorrhage, which is caused mainly by enhanced fibrinolytic-type disseminated intravascular coagulation (DIC). Although the true incidence of DIC in APL patients is unknown, a recent epidemiological survey conducted in Taiwan found that 90 (77.6 %) of 116 APL patients developed overt DIC [3].…”
Section: Introductionmentioning
confidence: 99%